The Moderating Effects of Technostress Inhibitors on Techno-Stressors and Employee's Well-Being - Hang, Yong; Hussain, Ghulam; Amin, Anam; Abdullah, Muhammad Ibrahim (Frontiers in Psychology, 2022)
This study determined the effects of techno-stressors on employees’ well-being. It also determined the moderating role of technostress inhibitors in techno-stressors and employees’ well-being. We employed a time-lagged design and self-administered survey method to collect data from banking employees. We retrieved 355 usable responses. The results showed that techno-stressors significantly and negatively affected employees’ well-being. Technostress inhibitors significantly and positively affected the employee’s well-being. The moderating effects of techno-stressors and technostress inhibitors showed that six of nine moderating effects were significant and positive. The results implied that technostress inhibitors help to improve employees’ well-being. In the end, we present some implications for theory and practice.